Crazy for God : how I grew up as one of the elect, helped found the Religious Right, and lived to take all (or almost all) of it back - Schaeffer, Frank (New York : Carroll & Graf, 2007)
Presents the autobiography of the son of evangelicals Francis and Edith Schaeffer, covering his career as an evangelical and the reason he left the faith to live a secular lifestyle
Includes index
Keywords: Schaeffer, Frank; Schaeffer, Frank; L'Abri (Organization); L'Abri (Organization); Evangelists -- United States -- Biography; Evangelicalism -- United States; Religious right -- United States; Evangelistic work -- United States -- Biography; Evangelicalism -- United States; Conservatism -- United States